PENATALAKSANAAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION DAN TRAKSI TRANSLASI TERHADAP PENURUNAN NYERI DAN PENINGKATAN ROM PADA CAPSULITIS ADHESIVE - Sinapa, Indri Kristanty; Mamuaja, Filly (Lasalle Health Journal, 2023)
Introduction: Capsulitis Adhesive is a condition characterized by inflammation of the shoulder joint capsule with limitation of shoulder range of motion in the form of a capsule pattern and pain in the shoulder joint. The main cause is not yet known with certainty, but secondary effects can be systemic, extrinsic or intrinsic. Capsulitis adhesive cases affect around 2% of the population with an age range of 40-60 years. The symptoms that appear in this case are pain, limited range of motion of the joints, decreased muscle strength, shoulder girdle muscle atrophy and impaired functional activities. Objective: to determine the effect of transcutaneous electrical nerve stimulation in reducing pain and the effect of traction - translation in increasing the range of motion of joints in patients with capsulitis adhesive. Methods: case study with a 64 year old male respondent who complained of shoulder pain and limited movement in the shoulder joint. Results: after receiving physiotherapy intervention 8 times for 4 weeks, there was a change in tenderness to 2, and movement pain from 4 to 2. The range of motion of the shoulder joint increased, exorotation motion from 30° to 50°, abduction motion 80° to 110°, and endorotational movement of 30° to 45°. Conclusion: Physiotherapy management in the form of transcutaneous nerve electrical stimulation and traction-translation has an effect on reducing pain and increasing the range of motion of the shoulder joint as well as increasing the functional ability of patients with capsulitis adhesive.